Hypertrophic Cardiomyopathy in Children: Pathophysiology, Diagnosis, and Treatment of Non-sarcomeric Causes - Monda, Emanuele; Rubino, Marta; Lioncino, Michele; Di Fraia, Francesco; Pacileo, Roberta; Verrillo, Federica; Cirillo, Annapaola; Caiazza, Martina; Fusco, Adelaide; Esposito, Augusto; Fimiani, Fabio; Palmiero, Giuseppe; et al. (Frontiers in Pediatrics, 2021)
Hypertrophic cardiomyopathy (HCM) is a myocardial disease characterized by left ventricular hypertrophy not solely explained by abnormal loading conditions. Despite its rare prevalence in pediatric age, HCM carries a relevant risk of mortality and morbidity both in infants and children. Pediatric HCM is a large heterogeneous group of disorders. Other than mutations in sarcomeric genes, which represent the most important cause of HCM in adults, childhood HCM includes a high prevalence of non-sarcomeric causes, including inherited errors of metabolism (i.e., glycogen storage diseases, lysosomal storage diseases, fatty acid oxidation disorders), malformation syndromes, neuromuscular diseases and mitochondrial disease, which globally represent up to 35% of children with HCM. The age of presentation and the underlying etiology significantly impact the prognosis of children with HCM. Moreover, in recent years, different targeted approaches for non-sarcomeric etiologies of HCM have emerged. Therefore, the etiological diagnosis is a fundamental step in designing specific management and therapy in these subjects. The present review aims to provide an overview of the non-sarcomeric causes of HCM in children, focusing on the pathophysiology, clinical features, diagnosis and treatment of these rare disorders.